Thai stakeholder's perceptions of the introduction of the Doctor of Pharmacy programme - Chanakit, Teeraporn (2016)
Global pharmacy education and pharmacy practice continue to face remarkable changes. Many countries are undergoing major transformations in the field of pharmacy education. In developing countries, there is an increasing trend towards adopting the PharmD degree. Thai pharmacy education has transitioned from having two entry-level degrees – a 5-year BPharm (with three main tracks: pharmaceutical care, pharmaceutical sciences, social and administrative pharmacy) and a traditional 6-year PharmD (pharmaceutical care) programme – to a single national 6-year PharmD programme or ‘an all-PharmD programme’ (including industry pharmacy and pharmaceutical care tracks).